CD44 promotes angiogenesis in myocardial infarction through regulating plasma exosome uptake and further enhancing FGFR2 signaling transduction - Qing Zhang; Li Chen; Liyi Huang; Hongxin Cheng; Lu Wang; Lin Xu; Danrong Hu; Chengqi He; Chenying Fu; Quan Wei (BMC, 2022)
Abstract Background Since angiogenesis occurs as the pathological process following myocardial infarction to alleviate ischemia, therapeutic angiogenesis has been proposed to be a cardioprotective strategy. CD44 has been implicated in endothelial cell functions and its role has been well established in angiogenesis for years. Although recent studies indicate the close correlation between CD44 and exosome, as well as the two being implicated in myocardial ischemia pathological processes, the effect and the underlying mechanism of CD44 and its regulated plasma exosome in pathological angiogenesis post-myocardial infarction have not been fully elucidated. Methods In this study, we used CD44 knockout mice to study the in vivo impacts of CD44 on ischemic angiogenesis in myocardial infarction. Mouse cardiac function was measured by echocardiography, histological changes were observed by Evans Blue and TTC-double staining and Masson's trichrome staining, and molecular changes were detected by immunofluorescence. In the in vitro study, CD44 knockout HUVECs were generated and CD44 inhibitor was used to study the mechanism of CD44 on angiogenesis. We performed the immunoprecipitation, proximity ligation assay, and super-resolution imaging to study the mechanistic regulation of FGFR2 signaling transduction by CD44. Importantly, we also isolated plasma exosomes from myocardial infarction model mice and studied the effect of plasma exosomes on the activation of the FGFR2 signaling pathway and the related phenotypic alterations, including exosomes uptake and angiogenic function in primary mouse microvascular endothelial cells, and further discovered the regulation mechanism of exosomal miRNAs. Results We observed that the expression of CD44 in the border zone of the infarcted heart was tightly related to pathological angiogenesis following myocardial ischemia. The depletion of CD44 impaired angiogenesis and impacts biogenesis and proangiogenic function of plasma exosomes. Subsequently, we found that CD44 mediated the activation of the FGFR2 signaling pathway as well as the caveolin 1-dependent uptake of exosomes in vascular endothelial cells. Most importantly, the proangiogenic therapeutic effect of plasma exosomal miRNAs depended upon the participation of CD44/FGFR2 signaling transduction in vascular endothelial cells. Conclusion CD44 and its regulated plasma exosomes have crucial potent angiogenic activity. Our studies elucidate that CD44 plays a key role in plasma exosomal miRNA-enhanced angiogenic FGFR2 singling transduction and ischemic angiogenesis in the early stage of myocardial infarction.